Effects of two triterpenoids from Nigella sativa seeds on insulin resistance of 3T3-L1 adipocytes - Wei, Jinfeng; Wang, Baoguang; Chen, Yixiao; Wang, Qiuyi; Ahmed, Adel F.; Cui, Lili; Xi, Xuefeng; Kang, Wenyi (Frontiers in Nutrition, 2022)
Insulin resistance (IR) is a physiological abnormality that occurs when insulin fails to activate the signal transduction pathway in target organs. It was found that supplementation of Nigella sativa seeds with oral antidiabetic medicines helps improve blood glucose control by enhanced β cells activity and alleviation of IR. However, the activities and related mechanisms of phytochemicals from N. sativa seeds have not been thoroughly explored. In this study, the effects of two triterpenoids, 3-O-[β-D-xylopyranose-(1→3)-α-L-rhamnose-(1→2)-α-L-arabinose]-28-O-[α-L-rhamnose-(1→4)-β-D-glucopyranose-L-(1→6)-β-D-glucopyranose]-hederagenin (Hxrarg) and 3-O-[β-D-xylopyranose-(1→3)-α-L-rhamnose-(1→2)-α-L-arabinose]-hederagenin (Hxra), on IR were studied by 3T3-L1 adipocytes model. The results demonstrated that Hxrarg and Hxra inhibited maturation of 3T3-L1 preadipocytes, dramatically stimulated glucose uptake of IR-3T3-L1 adipocytes, promoted transcription of IRS, AKT, PI-3K, and GLUT4 mRNA. Western Blot results suggested that Hxrarg and Hxra were able to markedly up-regulate expression of p-IRS, p-AKT, PI-3K, and GLUT4 proteins. These findings could provide a basic foundation for the continued development and application of N. sativa in medicine and functional foods.